RESHIS OF THE KASHMIR VALLEY: A CASE STUDY OF BABA SHAKUR-UD-DIN WALI R.A - Ishfaq Ahmad Mir (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Abstract Kashmir commonly referred to as "heaven on earth," is home to countless mystics, saints, sufis, and reshis. The word "Rishi" itself is unmistakably derived from Sanskrit and Indian customs. The Rishi Silsilah in Kahmir was founded by Sheikh Nuruddin. Akbar Nama of Abul Fazl, a significant historian from that time, praises them. He states, "Reshis are the most respected class of people in Kashmir Valley." They are sincere in their worship, even if they haven't given up on the conventional and traditional forms of worship (taqlid). They do not disparage men who practice other religions. They lack the tongue of desire and do not pursue material possessions. In order for humans to profit from these, they grow fruit-bearing trees. They avoid eating meat and getting married.